Seneca the Elder and his rediscovered ›Historiae abinitio bellorum civilium‹ New Perspectives on Early-Imperial Roman Historiography - Scappaticcio, Maria Chiara (De Gruyter, 2020)
This is the first volume dedicated exclusively to the historiographical work by Seneca the Elder, after the recent discovery of a fragmentary roll from Herculaneum bearing traces of his Historiae. Contributions not only focus on the discovery of the papyrus roll, but also offer a broader view on early-imperial Roman historiography, to which the new perspectives opened by the rediscovery of Seneca the Elder's Historiae greatly contribute.